2020
DOI: 10.1111/jmi.12864
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution imaging of the human incudostapedial joint using synchrotron‐radiation phase‐contrast imaging

Abstract: Summary The incudostapedial joint (ISJ) of the middle ear is important for proper transmission of sound energy to the cochlea. Recently, the biomechanics of the ISJ have been investigated using finite‐element (FE) modelling, using simplified geometry. The objective of the present study was to investigate the feasibility of synchrotron‐radiation phase‐contrast imaging (SR‐PCI) in visualising the ISJ ultrastructure. Three human cadaveric ISJs were dissected and scanned using SR‐PCI at 0.9 µm isotropic voxel size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…High-resolution imaging of human cartilage with X-PCI is reported in recent literature to reach a micron resolution [ 37 , 38 ], which only depicts the cell distribution. Therefore, another innovation is that nano-tomography achieves a sub-micron resolution, which enables depiction of details within a single cell and for the first time as a radiographic technique the depiction of tissue density variations around chondrocytes corresponding to a differing biochemical composition (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution imaging of human cartilage with X-PCI is reported in recent literature to reach a micron resolution [ 37 , 38 ], which only depicts the cell distribution. Therefore, another innovation is that nano-tomography achieves a sub-micron resolution, which enables depiction of details within a single cell and for the first time as a radiographic technique the depiction of tissue density variations around chondrocytes corresponding to a differing biochemical composition (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The synchrotron-based PhC-microCT has enabled the high-contrast visualization of the middle ear [30]; indeed, recently, it was shown that this technique can be successfully applied to image the ultrastructural characteristics of the human incudostapedial joint [31].…”
Section: Auditory Apparatusmentioning
confidence: 99%
“…In addition to laboratory or clinical micro-CT scanners [20,21], static synchrotron-based X-ray microtomography has allowed new morphological studies of the inner and middle ear. By harnessing the unique properties of synchrotron radiation, this technique provides enhanced spatial resolution and soft tissue contrast by exploiting phase contrast in addition to absorption contrast, making it ideal for investigating delicate anatomical structures without destruction [22][23][24]. More recently, we were also able to perform dynamic synchrotron-based X-ray microtomography for the rst time on unstained fresh-frozen human ear specimen and extract the threedimensional information of the dynamic behavior of the auditory ossicles during sound stimulation of 110 dB and 120 dB SPL at 128 Hz [25].…”
Section: Introductionmentioning
confidence: 99%